2017
DOI: 10.1155/2017/6913106
|View full text |Cite
|
Sign up to set email alerts
|

Association of Paraoxonase-1 Q192R (rs662) Single Nucleotide Variation with Cardiovascular Risk in Coffee Harvesters of Central Colombia

Abstract: Paraoxonase 1 (PON1), a high-density lipoprotein-associated antioxidant enzyme, hydrolyzes several organophosphate pesticides and oxidized lipids. The PON1 Q192R polymorphism affects the catalytic efficiency and is considered a risk factor for pesticide intoxication and cardiovascular disease (CVD) but the association is not consistent between individuals or populations. We aimed to study the association of PON1 Q192R polymorphism with CVD risk in coffee harvesters of central Colombia. Demographics were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…This work researched the polymorphisms mentioned (Q192R, L55 M, and C-108T). The results show that the allelic and gene frequencies of these polymorphisms ( Table 3 ) do not differ much from those found in the North American [ 23 ], Latin [ 24 , 25 ], and even Colombian populations [ 26 ].…”
Section: Discussionmentioning
confidence: 69%
“…This work researched the polymorphisms mentioned (Q192R, L55 M, and C-108T). The results show that the allelic and gene frequencies of these polymorphisms ( Table 3 ) do not differ much from those found in the North American [ 23 ], Latin [ 24 , 25 ], and even Colombian populations [ 26 ].…”
Section: Discussionmentioning
confidence: 69%
“…PON1 rs662 gene polymorphism is involved in modulating the PON1 enzyme 23 . The R allele variant is implicated in the less active isoform of PON1 against lipoprotein oxidation, and higher ox-LDL, triglycerides, and LDL-C, which lead to an increased risk of vascular dysfunction 24 , 25 . Moreover, the inter-relationship between the PON1 and PON2 genes may affect glycaemic control in patients with diabetic retinopathy 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The R allele variant has been associated with a less active isoform of PON1 against lipoprotein oxidation, resulting in an enhanced risk of vascular disease [40]. A meta-analysis study found that the R allele gene variant is significantly associated with increased levels of ox-LDL, triglycerides, total cholesterol, and LDL-C, which may lead to a higher risk of CAD [22].…”
Section: Discussionmentioning
confidence: 99%